Integrasi Sains Dan Agama Dalam Pendidikan Islam - Nasiruddin . (LITERASI (Jurnal Ilmu Pendidikan), 2013)
Discuss the issue of science and religion, we would come to the discussion of the interaction of science and religion at the same time meaningful symbolic level. In geneologis we can see the complexity of the interaction of religion and science in the debate between faith dimension textually understood and understand the marginalizing science because of religious doctrine often considered incompatible with the common sense arguments. Though science and religion born from the same womb that is the "experience" of humanity. Up to now, there are still strong presumption in the wider community who say that "religion" and "science" are two entities that can not be met. Both have their respective areas, separated from each other, both in terms of formal object-material, research methods, criteria of truth, the role played by scientists. Key words : Integration, interaction of science and religion